The Role of the Young Generation in Medan City with Analysis of the Determinants of Consumptive Behavior - Ade Gunawan; M Firza Alpi; Bunga Paramitha (International Journal Reglement & Society (IJRS), 2023)
This research aims to find out the influence of Financial Literacy, Financial Technology and Lifestyle on Consumptive Behavior among the Young Generation in Medan City. The approach used is quantitative. The population in this study was the younger generation in the city of Medan, totaling 2,494,512 people, while this research method used the Slovin formula, so that a sample of 100 people was obtained. This research instrument uses a questionnaire. The data analysis technique uses Statistical Package for the Social Sciences (SPSS) version 29. The research results show that Financial Literacy has a significant effect on Consumptive Behavior. Financial Technology has no significant effect on Consumptive Behavior, and Lifestyle has a negative effect on Consumptive Behavior. Meanwhile, simultaneously Financial Literacy